DIABETIC NEUROPATHY: INNOVATIVE TREATMENT TECHNIQUES - Mihaela Alina Calin; Ana Magdalena Bratu; Adrian Petru Radu; Burduloi Vlăduț Mirel; Camelia Ana Grigore; Cristian Iorga; Cristina Raluca Iorga (Romanian Society of Oral Rehabilitation, 2023)
Diabetic neuropathy represents a frequent and debilitating complication of diabetes, affecting the peripheral nervous system and contributing to symptoms such as pain, tingling, and numbness. In this review, we explore innovative treatment techniques that have been studied to alleviate the symptoms of diabetic neuropathy. Key aspects covered include low-level laser therapy (LLLT), transcutaneous electrical nerve stimulation (TENS), the use of antiepileptic and antidepressant medications, stem cell therapy, and the integration of virtual reality in pain therapy. LLLT has shown promise in stimulating nerve regeneration, while TENS provides a non-invasive approach to managing neuropathic pain. Antiepileptic and antidepressant medications have demonstrated significant benefits, and stem cell therapy is at the forefront of research for tissue regeneration. Additionally, the integration of virtual reality in pain therapy offers an innovative perspective, distracting patients from their symptoms and improving their quality of life. Managing diabetic neuropathy extends beyond conventional therapies, evolving constantly through the integration of innovative techniques with the potential to significantly enhance the quality of life for affected patients. It is essential to continue research and rigorously evaluate the effectiveness of these approaches, collaborating with healthcare professionals to provide personalized and efficient solutions.